2006
DOI: 10.1111/j.1365-2230.2006.02106.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the plasma level of vitamins A and E affect acne condition?

Abstract: Based on our results, we conclude that low vitamin A and E plasma levels have an important role in the pathogenesis of acne and in the aggravation of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 19 publications
1
40
1
1
Order By: Relevance
“…Additionally the antibiotics are becoming less and less useful as resistant strains of P. acnes are becoming more common, and the acne will generally reappear relatively soon after the end of treatment, days later in the case of topical applications, and weeks later in the case of oral antibiotics. Other less wellestablished procedures include the use of hormonal treatments (cortisone), topical or oral retinoid use (vitamin A-related compounds [6]) and phototherapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the antibiotics are becoming less and less useful as resistant strains of P. acnes are becoming more common, and the acne will generally reappear relatively soon after the end of treatment, days later in the case of topical applications, and weeks later in the case of oral antibiotics. Other less wellestablished procedures include the use of hormonal treatments (cortisone), topical or oral retinoid use (vitamin A-related compounds [6]) and phototherapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the blood concentration of β-CRX has been reported to be higher than that of β-carotene or lycopene [47], it is suggested that β-CRX is easily absorbed and accumulated in the skin, where it may behave as Vitamin A for the control of cutaneous functions. Taken together with a report of El-Akawi et al [28] that low plasma levels of Vitamin A are associated with acne development and aggravation, therefore, the supplementation of β-CRX is likely to be effective for the prevention of acne or acne maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, epidemiologic studies have shown that higher intakes or blood levels of β-CRX result in a reduced risk of lung cancer and rheumatoid arthritis development [25][26][27]. On the other hand, it has also been reported that low plasma level of Vitamin A is associated with the development and aggravation of acne [28]. In addition, β-CRX is a vitamin A precursor, which is oxidatively cleaved to vitamin A by β-carotene 15,15'-dioxygenase [29], and can be stably stored in some tissue for several months [30].…”
Section: Introductionmentioning
confidence: 99%
“…There are many common treatments for acne lesions including drugs, over the counter products and procedures such as laser therapy [24]. There has also been an increasing interest in the use of natural products for skin health such as vitamin C, other antioxidants, botanicals and omega-3 fatty acids [5, 6]. One agent that has shown promise in reducing facial acne lesions is pantothenic acid (vitamin B 5 ).…”
Section: Introductionmentioning
confidence: 99%